Um mar de narrativas: uma análise estrutural da animação Moana - um mar de aventuras (2016) - Pinheiro, Rhaabe Gazziero (2024)
This work investigates the possibility of reading and applying the narrative structure proposed by Roland Barthes in the essay An Introduction to the Structural Analysis of Narratives (2011), especially in the animated film genre. The film Moana (2016) was chosen as the object of analysis. To deepen the methodology, in addition to Barthes, we use concepts from authors such as Nelly Novaes Coelho in her work on studies of Vladimir Propp, Walter Benjamin, Umberto Eco, Anatol Rosenfeld, and James Wood. The research is divided into two chapters. The first presents, in more detail, the three levels of narrative description: functions, actions and narration, and explains that, although we follow Barthes’ principles, the order will be reversed, as we consider narration to be the central element in the reading of a film. This chapter also discusses the film as a story being told, including the use of myths, legends, and tales from oral tradition culture. The analysis takes place in the second chapter, which is divided into three subsections, each dedicated to the reading of one level of the narrative. From this analysis, it was concluded that animation can be interpreted in a manner similarly to a literary text, following structural analysis methods.